Prácticas desleales y sus efectos en la industria del acero mexicano - García González, Daira Daniela (2024)
Up until August 2023, twenty-nine steel producers in Mexico have requested the Economic Secretary to investigate unfair trade practices in steel imports. This study explores the impact of these practices on the Mexican steel industry. We analyzed reports of investigations of unfair trade practices published by the National Chamber of the Steel and Iron Industry and conducted interviews with steel producers. Through exploratory data analysis and qualitative open content coding, we found that the importation of steel under unfair trade practices caused a reduction in internal sales ranging from -9% to -23%. Additionally, these practices decreased the operative margin between -6.9% and 57% of the national steel producers, depending on the steel product. On the other hand, the steel industry is highly capital-intensive, and the effects of these practices lead to the generation of idle capacity. The Economic Secretary has applied compensatory duties to counteract the damage and protect the national steel industry. Nevertheless, the effects on industries that use steel as an intermediate good are being questioned. It is necessary to consider alternative solutions that do not rely solely on implementing protectionist measures.